2014
DOI: 10.1007/s00167-014-2926-4
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous cartilage of human menisci is less shock-absorbing and energy-dissipating than hyaline cartilage

Abstract: In dynamic measurements with a spherical indenter, the menisci are much softer and less energy-dissipating than hyaline cartilage. Further, the menisci are stiffer and less energy-dissipating in the middle, intermediate part compared to the meniscal base. In compression, the energy dissipation of meniscus cartilage plays a minor role compared to hyaline cartilage. At high impacts, energy dissipation is less than on low impacts, similar to cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
1
19
0
3
Order By: Relevance
“…Low fibrillar stiffness, high permeability, and reasonably high nonfibrillar matrix modulus help tissue deformations and dissipation under prolonged loading conditions. It may be that the meniscus, which was not considered here, may be the elastic shock absorber in the knee while the tibial plateau cartilage contributes primarily to the viscous dissipation of loads (Danso et al, 2015;Gaugler et al, 2014;Pereira et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Low fibrillar stiffness, high permeability, and reasonably high nonfibrillar matrix modulus help tissue deformations and dissipation under prolonged loading conditions. It may be that the meniscus, which was not considered here, may be the elastic shock absorber in the knee while the tibial plateau cartilage contributes primarily to the viscous dissipation of loads (Danso et al, 2015;Gaugler et al, 2014;Pereira et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…For example, it has been shown that hyaline cartilage serves as a better shock absorber than fibrous menisci. 28 This finding suggests that a loss of cartilage may induce a reduced shock absorption capacity of the joint, increasing loads on the subchondral bone. Moreover, anterior cruciate ligament (ACL) lesions have been shown to alter knee kinematics.…”
mentioning
confidence: 99%
“…In 2009, Bursac et al showed that collagen content, proteoglycan content, and tensile properties of menisci from donors younger than 45 years old were not agedependent [21]. Shock absorption properties of fibrous cartilage in the meniscus were later studied in 2015 [22]. The authors observed that the dynamic modulus of elasticity in hyaline cartilage was approximately ten times higher than that in the meniscus, while the loss angle in fast indentation stayed at the range of hyaline cartilage.…”
Section: Collagen Fiber Viscoelasticity and Shock Absorptionmentioning
confidence: 99%